Maliseet materials, Frank Siebert Papers - Burlin, Natalie Curtis, 1875-1921; Mechling, William Hubbs, 1888-1953; Nicholas, Andrea Bear; Sands, Donald B.; Sherwood, David; Siebert, Frank T. (Frank Thomas), 1912-1998 (1907)
The Maliseet materials in the Siebert Papers consist primarily of secondary sources in Series IV and VII . Siebert's work can be found in Series V. Of special interest are a collection of Maliseet tales from 1914 collected by William Mechling.